Land redistribution and poverty alleviation in South Africa - Mukarati, J.; Mongale, I. P.; Makombe, G. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
Land is viewed as the main source of livelihood for the majority of rural households in developing countries. However, the majority of the rural households do not have access to productive lands as land is finite and therefore a scarce resource and its distribution is largely attributed to historical land imbalances, hence the problem of rural poverty is more prevalent among the rural households. There has been increased demand for land for livelihoods and various land policies have been implemented in developing countries to stimulate growth in the agricultural sector and alleviate rural poverty. The question that remains is how does land redistribution policies and agriculture growth affect poverty alleviation? To answer the question, this study employed a multiplier decomposition approach using the 2010 IFPRI SOCIAL accounting matrix as the data base. The multiplier decomposition approach revealed that land redistribution and agriculture growth can alleviate poverty in South Africa. However, for significant poverty alleviation, only long- term land reform policies geared toward improving agricultural productivity and growth should be implemented.
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Multiplier decomposition; Land policies; Poverty alleviation; rural household; Land reform